PLAGIARISM AS A WIDESPREAD PHENOMENON AMONG SECOND-LANGUAGE LEARNERS AT TBILISI STATE UNIVERSITY - Baratashvili, Ina; Kikilashvili, Manana (Online Journal of Humanities ETAGTSU, 2021)
Plagiarism is claimed to plague academic realm on a world scale. Georgia is no exception in that respect. Tbilisi State University (TSU) is taking the issue of plagiarism very seriously which is manifested in the measures adopted by the institution to tackle the problem. The university policies regarding plagiarism viewed as a phenomenon of an academic misconduct are constantly becoming stricter and stricter. The article deals with one of the forms of plagiarism used by TSU students in their assignments, specifically, in their presentations. Presentations, an obligatory form of assessment in nearly all syllabi at the university are frequently characterized by poor referencing, inaccurate citation, when often the whole chunks of text are directly taken from the original sources without any periphrasis or indication of the source. The research focuses on aforementioned instances of plagiarism, their causes and strategies for solving the problem. As a part of conducted research were studied presentations prepared by students at two different faculties (Humanities and Economics) doing English language courses (General English and EAP). Also, students were interviewed online. <a title="Plagiarism As A Widespread Phenomenon Among Second-Language Learners At Tbilisi State University" href="https://etag.tsu.ge/journal/files/06_Ina-Baratashvili,-Manana-Kikilashvili.pdf" target="_blank" rel="noopener">Full Text (PDF)